A Synthesis of Information on Regulation, Organization and Methodology of Audit in the EU Countries - V. PANTELEIEV (Naukovij Vìsnik Nacìonalʹnoï Akademìï Statistiki, Oblìku ta Auditu, 2019)
The paper sums up documents on the legal and practical framework for the regulation of audit, quality control of audit services and public oversight audit all countries of EU. For more than a quarter of a century, an understanding and approval practice of providing audit services has been formed in Ukraine. As an important element of the market mechanism, an audit involves expressing the reasoned opinion of an independent, qualified professional about the entity's financial statements. The time requirement is the use by regulators of new, modern audit techniques. Audit development in Ukraine always goes hand in hand with the study and use of positive audit experience in market economy countries. The main components of such techniques are certain procedures for auditing, quality control of audit services and public oversight bodies. The paper on legal acts and literary sources summarizes the legal and the best practices of audit regulation, quality control of audit services and public oversight bodies in all EU countries (currently 28). The tendencies of organization and regulation of audit activity, variants of influence on the quality of audit services, as well as application of state and non-governmental levers of forming the body of public supervision are indicated. A critical attitude to the regulation of audit, organization and methods of audit in Ukraine is justified. Conclusions are drawn and prospects for further research are outlined.